Stick-Slip Dynamics in a Granular Material With Varying Grain Angularity - Kozlowski, Ryan; Zheng, Hu; Daniels, Karen E.; Socolar, Joshua E. S. (Frontiers in Physics, 2022)
Experiments, simulations, and theoretical treatments of granular materials typically feature circular or elliptical grains. However, grains found in natural systems often have flat faces that introduce local rotational constraints; these rotational constraints have been shown to affect, for example, the jamming transition, discontinuous shear thickening, and ordered states in colloids and thermalized grains. In this work, we experimentally investigate the effects of grain angularity on stick-slip dynamics. A weighted slider is pulled by a spring over a gravity-packed granular bed composed of polygonal grains with varying angularity. We find that packings of triangular or square grains have higher shear strengths than packings of pentagons, hexagons, heptagons, or disks. Additionally, as the number of sides increases, sticking periods, during which the slider remains motionless while the spring force on it increases, become shorter on average, with the material yielding at smaller applied stresses. Lastly, we find that dilation of the medium during sticking periods tends to be larger for grains with higher angularity, in part because of the presence of stilt-like columnar structures that prop the slider up. We report on measurements of the pulling force on the slider, particle dynamics during slip events, and properties of force-bearing contact networks identified via photoelasticity. Our findings indicate that high angularity of grains (pentagons, squares, triangles) leads to differences in grain-scale flow and macroscopic stick-slip dynamics of bulk granular materials. Our experiments also indicate a continuous change in dynamics with decreasing angularity as the circular grain limit is approached.